'Talvez nunca mais eu veja minha terra natal' : a trajetória de imigrantes alemães na colonização de Porto Novo/SC (1932-1942) - Schneider, Maikel Gustavo (2018)
The purpose of this study is to investigate, from the perspective of micro history, the trajectory of a group of German immigrants who emigrated from Germany to Brazil between 1932 and 1940, settled in the Porto Novo colony. The municipalities of Itapiranga, São João do Oeste and Tunápolis - located in the region of Extremo Oeste in the state of Santa Catarina – now compose this territory. The Porto Novo colonization project was planned, organized and promoted by the Volksverein für die Deutschen Katholiken in Rio Grande do Sul - Sociedade União Popular para Alemães Católicos no Rio Grande do Sul (Popular Union for Catholic Germans in Rio Grande do Sul), an entity founded by the Jesuit priests, and implanted in 1926 beside the Uruguay River. It was a colony aimed at German Catholics who received, in the first years, a significant number of migrants from the colonies of Rio Grande do Sul. From 1932, motivated by the propaganda carried out in Germany, especially a brochure written about Porto Novo circulated in different regions, and in the context of post World War I, a group of Germans, with predominantly urban profile, emigrated and settled in the colony, specifically in the Line President Becker. Thus, it is our objective to investigate and understand these migratory trajectories, the challenges faced by immigrants, as well as the reasons for their displacement, as well as eventual return processes to the native land, analyzing the context of departure and arrival. Therefore, the study seeks to trace the trajectory of these families, in the game of scales, in the context of human transoceanic mobility and the insertion in the place of arrival, with the adaptation of their way of life to the colony – the departure, the arrival and the permanence. The pertinence of the study lies in the fact that the historiography about the state of Santa Catarina marginally addresses the German immigration of the early twentieth century, making little distinction between settlers who are the result of internal migration and immigrants. Therefore, the study allows to affirm that these immigrants, the majority urban workers, had good financial conditions, being the spontaneous emigration an option, the capital brought by them assured the acquisition of a colonial lot and the initial installation in that new space. It signals for a spontaneous and heterogeneous migratory flow and for the most diverse motivations, which can be verified from the study of trajectories.